Critical Dispositions in Controversial Science Issues: Evidence From Science Education Students within the Context of the PISA 2025 Science Framework - Alqadri, Zulqifli; Munawwarah, Munawwarah; Husain, Najwa Ashilah; Annam, Syarful (JURNAL BIOEDUKASI, 2025)
Critical disposition is a crucial element in 21st-century science education, particularly in addressing controversial scientific issues across personal, societal, and global contexts. However, limited research has examined how these dispositions develop within internationally oriented programs such as the International Class Program (ICP) in Indonesia. This study aims to describe and compare the profiles of students’ critical dispositions across Facione’s seven indicators: Truth-Seeking, Open-Mindedness, Analyticity, Systematicity, Critical Thinking Self-Confidence, Inquisitiveness, and Maturity of Judgment within controversial science issues at personal, local/national, and global scales. A quantitative descriptive method was employed involving 114 ICP Science Education students from cohorts 2022 to 2025. The 21-item Science Critical Disposition Test (SCDT) (CVI = 0.83; α = 0.78) was used to measure the seven indicators based on Facione’s framework integrated with the PISA 2025 science contexts. The results revealed that all indicators were categorized as very high, with Open-Mindedness showing the highest mean score and Analyticity and Inquisitiveness the lowest. Across contexts, critical dispositions were strongest in personal issues, slightly lower in local/national issues, and lowest in global issues. These findings indicate that contextual familiarity enhances students’ engagement in critical reasoning, while global issues require higher analytical effort. In conclusion, ICP students demonstrated strong critical dispositions consistent with the PISA 2025 framework.